(untitled) - Ivancevich, John M. (Boston, MA., 2005)
Organizational Behavior and Management’s new chapters examine perceptual biases and emotional dispositions along with management of workplace misbehavior, while interconnecting themes now integrate global practice, the balancing of work/life responsibilities, and benchmarking for competitive advantage.
Keywords: Organizational behavior